Ways to ensure financial security of the money-credit sector - Jo’rayev Og’abek Oybek o’gli (Open Academia, 2023)
Financial security involves having enough money to comfortably cover your monthly expenses, recover from financial setbacks, and save for your future. It's also about having low financial stress and feeling in control of your money